Clinical and Immunological Factors Associated with Recommended Trough Levels of Adalimumab and Infliximab in Patients with Crohn’s Disease - Orts, Beatriz; Gutierrez, Ana; Madero, Lucía; Sempere, Laura; Frances, Ruben; Zapater, Pedro (Frontiers in Pharmacology, 2022)
Introduction: Up to 40% of patients with Crohn’s disease do not respond to treatment with anti-TNF or lose response after the initial benefit. Low drug concentrations have been proposed as the main predictor of treatment failure. Our aim was to study the immunological profile and clinical evolution of patients with Crohn’s disease according to the anti-TNF dose and serum trough levels. Methods: Crohn’s disease patients in remission treated with infliximab or adalimumab at stable doses for at least for 3 months were included. Serum levels of anti-TNF, TNF-α, interferon-γ, and interleukin IL-12, IL-10, and IL-26 were determined in blood samples taken just before drug administration. Patients were classified according to anti-TNF levels below, within, or above the target level range and the use of intensified doses. Clinical evolution at 6 months was analyzed. Results: A total of 62 patients treated with infliximab (8 on intensified schedule) and 49 treated with adalimumab (7 on intensified schedule) were included. All infliximab-treated patients showed levels within the recommended range, but half of adalimumab-treated patients were below the recommended range. A significant negative relationship between body weight and adalimumab levels was observed, especially in patients treated with intensified doses. Patients with infliximab levels over 8 µg/ml presented higher median IL-10 than patients with in-range levels (84.0 pg/ml, interquartile range [IQR] 77.0–84.8 vs. 26.2 pg/mL, IQR 22.6–38.0; p < 0.001), along with lower values of interferon-γ (312.9 pg/ml, IQR 282.7–350.4 vs. 405.6 pg/ml, IQR 352.2–526.6; p = 0.005). Patients receiving intensified versus non-intensified doses of infliximab showed significantly higher IL-26 levels (91.8 pg/ml, IQR 75.6–109.5 vs. 20.5 pg/ml, IQR 16.2–32.2; p = 0.012), irrespective of serum drug levels. Patients with in-range levels of adalimumab showed higher values of IL-10 than patients with below-range levels (43.3 pg/ml, IQR 35.3–54.0 vs. 26.3 pg/ml, IQR 21.6–33.2; p = 0.001). Patients treated with intensified vs regular doses of adalimumab had increased levels of IL-12 (612.3 pg/ml, IQR 570.2–1353.7 vs. 516.4 pg/mL, IQR 474.5–591.2; p = 0.023). Four patients with low adalimumab levels (19%) and four treated with intensified doses were admitted to a hospital during a follow-up compared to none of the patients with levels within the range. Conclusion: Patients with Crohn’s disease treated with infliximab and adalimumab exhibit differences in serum levels of cytokines depending on the drug, dose intensification, and steady state trough serum levels.